Risk of Biopsy and Surgical Treatment of Subglottic Paragangliomas: A Case Report - Xi‐Ming Zhao; Liang Tang; Jun Liu; Yong‐Hai Luo; Shi‐Ling Xiong; Jiao Cui (Clinical Case Reports)
ABSTRACT This report describes a rare case of a paraganglioma occurring beneath the vocal folds. During the preoperative biopsy, we encountered significant hemorrhage, forcing us to stop the procedure and preventing us from obtaining a definitive diagnosis. Despite these challenges, the eventual surgery had a good outcome.